FRONT AND BACK MATTER VOL. 5 NO. 2 - N N (Universitas 17 Agustus 1945 Surabaya, Prodi sastra Inggris, Fakultas Ilmu Budaya, 2022)
Anaphora: Journal of Language, Literary, and Cultural Studies is a double-blind peer-reviewed journal, open access, and biannual academic journal dedicated to the publications of research in the areas of language, literary, and culture studies. Language studies may include issues in applied linguistics such as socio-linguistics, discourse analysis, critical discourse analysis, pragmatics, stylistics, corpus linguistics and so forth. Literary studies covers English classics, modern and contemporary literature in the forms of printed, screened, aired or performed texts, comparative literature, children literature, sociology of literature, structuralism, psychoanalysis and so forth. Cultural studies cover cultural texts and practices, especially those associated with issues about language and literature, such as gender criticism, media studies, popular culture, and so forth. Its primary objective is to provide a forum for scholars and practitioners in the areas to address such issues. To be selected for publication, the manuscript should present new ideas in the disciplines, originated from empirical, theoretical, and methodological research within both a single discipline and those that sub- or multi-disciplines. This journal encourages a high standard of scholarship, written in a clear and straightforward organization without requiring that authors alter their analytical style and writing voice. Anaphora: Journal of Language, Literary, and Cultural Studies is scheduled for publication twice a year in JULY and DECEMBER. Anaphora: Journal of Language, Literary, and Cultural Studies is SINTA 4 accredited by Ministry of Education, Culture, Research, and Technology / Directorate General of Higher Education, Research, and Technology, from Volume 2, No. 1 to Volume 6, No. 2. Regarding No. 164/E/KPT/2021